Circulating T cell subsets in the Lambert-Eaton myasthenic syndrome. Issue 6 (June 1985) - Robb, S A; Bowley, T J; Willcox, H N; Newsom-Davis, J
Abstract : Peripheral blood T cell subsets were measured using monoclonal antibodies and a fluorescence activated cell sorter in 15 untreated patients with Lambert-Eaton myasthenic syndrome (nine with small cell carcinoma, one undifferentiated epithelial tumour (ca-LEMS], five with no demonstrable tumour (non-ca-LEMS), 10 age-matched healthy controls and 10 patients with small cell carcinoma without neurological disease. OKT8+ (suppressor/cytotoxic) T cells were significantly decreased in ca-LEMS compared with non-ca LEMS (p less than 0.001) ca-controls (p less than 0.01) and healthy controls (p less than 0.001). In one patient depressed OKT8+ T cells antedated clinically evident tumour by five months. OKT3+ (total) and OKT4+ (helper) T cells were similar in ca-LEMS, non-ca LEMS and controls. The mechanism underlying the loss of circulating OKT8+ T cells in ca-LEMS is unknown, but these changes may help to predict the presence of carcinoma in this disease.